Tracking Patient Outcomes Following Foot and Ankle Surgery: The OFAR Experience 2018-2019. Issue 4 (16th October 2019) - Hunt, Kenneth; Benthien, Ross; Baumhauer, Judith F.; DiGiovanni, Christopher; Challa, Shanthan; Guss, Daniel; Karr, Scott; Latt, L. Daniel; Moon, Daniel; Network, The OFAR
Category: Patient Reported Outcomes Introduction/Purpose: Collection and reporting of Patient Reported Outcomes (PROs) has become an integral part of healthcare and healthcare research. In an effort to facilitate AOFAS member participation in secure and efficient patient outcomes data collection, the Orthopaedic Foot and Ankle Outcomes Research (OFAR) Network, a national collaborative surgical outcomes registry, was established in 2018 by and for AOFAS member surgeons and their patients. OFAR aims to collect, aggregate, and report PRO data using the measurement instruments developed by the National Institutes of Health (NIH) Patient Reported Outcomes Measurement Information System (PROMIS). We hypothesize that multiple sites from a variety of health systems can successfully enroll patients into a secure, web-based registry, and that foot and ankle procedures will significantly improve patient reported function and pain. Methods: Since December 2018, seven OFAR pilot sites have been enrolling patients, including three private and four academic practices. Each enrolled patient completed a pre-operative assessment as well as post-operative assessments at 3 time points. Five PROMIS metrics were collected, including Physical Function CAT (PF), Pain Intensity Short Form (PInSF), Pain Interference CAT (PInCAT), Global Health Short Form, and Depression CAT. Pathways, a secure web platform accessible by both patients and providers, was utilized for data collection and storage. The platform also includes a provider dashboard that collects diagnosis, treatment, implant and complication data. The aggregated data was analyzed using Python (v3.6) along with Pandas (v0.23.4). Results: As of December 2018, 877 patients have been enrolled in OFAR. Patients were enrolled from both academic (57%) and private practice (43%) sites. The three most frequently encountered conditions were: ankle impingement, ankle fractures and ankle arthritis. The largest pre- to postoperative changes were seen in the PF and PInCAT scores which significantly improved at 6 months and 12 months for nearly all condition groups (Figure 1). Many of these improvements averaged 20 points on the PROMIS t-score scale, which represents two standard deviations in the PROMIS scoring system, and restored PInCAT and PF to 50 or better, the US healthy population average. There was a trend toward improvement in depression scores for most conditions, with substantial improvement following fracture treatment. Conclusion: We were able to successfully onboard multiple pilot sites, including community private practices without dedicated research resources, to enroll patients in the OFAR platform. Aggregated data demonstrate a significant improvement in PROMIS scores for all conditions treated. The library of information collected is automated, extensive and comprehensive. By aggregating outcomes following treatment by orthopaedic foot and ankle surgeons across practice settings, the OFAR database empowers an unprecedented scrutiny of 'real world' patient outcomes and related factors. This facilitates an increasingly granular assessment of the impact of conditions and treatments, enabling patients and providers alike to share in the decision-making process.